Effect of Partial Substitution of Lanthanum (La) on the Structural and Electric Properties of Bi2Sr2Ca2Cu3xLaxO10+Î´ - Jassim, Kareem Ali; Hussein, Haider Sahi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the current study, we investigate the effect of  (La) substitution  instead of (Cu) on the properties of the superconductor compound  (Bi2Sr2Ca2Cu3-xLaxO10+Î´)  with (x=0,0.05,0.1,0.15,0.2). The samples were  prepared  by solid state reaction method(SSR). Xray diffraction technique (XRD) was used to estimate the structural  properties of the specimens which show an orthorhombic crystalline structure for all the specimens.       The results show that the change in ( La) concentration  leads to decrease the concentration of (Bi-2223), increment in (Bi-2212 ) and(Bi-2201) with appearance of some impurities. Also decrease the critical temperature(Tc) with the increase of ( La) concentration.